Pelatihan Penyusunan Soal Berfikir Tingkat Tinggi bagi Guru-Guru Matematika SMA di Jember - Didik Sugeng Pambudi; Reza Ambarwati; Dinawati Trapsilasiwi; Erfan Yudianto (Universitas Lancang Kuning, 2022)
One of the problems that occur in mathematical subjects was the ability for students to solve problems that need the Higher Order Thinking Skills (HOTS) still low. This problem also occurs in high school students (SMA) in Jember. The cause of the problem was that the mathematics teacher has not been skilled in making HOTS problems and has not guided students to solve HOTS problems. To overcome this problem, training activities followed by 118 high School Mathematics teachers held on 02 February 2019 at the center of MGMP (Teachers' discussion group) in Jember. The methods used were sharing information, discussions, and assignments to made HOTS mathematical problems, observation, test, and giving questioner. The results gained were the teacher's knowledge of the HOTS problem increasing from the average score of pretest 62 to the average score of posttest 85. The teacher's ability to make HOTS problems was already in good category, and all participants (100%) actively participate in training activities and give positive responses to the activity. The community services activity need to be continued in the future, because it is very important for improving teachers’ professionalism.